2001
DOI: 10.1038/sj.bdj.4801176a
|View full text |Cite
|
Sign up to set email alerts
|

Participating dentists' assessment of the pilot regional online videoconferencing in dentistry (PROVIDENT) project

Abstract: Objective To assess the educational effectiveness of delivering continuing professional education (CPE) from dental schools to small groups of dentists at distant sites via videoconferenced links using relatively inexpensive equipment and ISDN2 links. Design 41 videoconferences between the four campuses of London Dental Schools and postgraduate centres in South East England were assessed using a pre-piloted questionnaire which contained open and specific questions. The questionnaire was given to all participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Ninety percent of the 257 participants indicated that they would like to attend future educational sessions delivered by VC and expressed satisfaction about not having to travel for the sessions. 9 The results of the current study corroborate these findings and extend them to an audience of school professionals and content related to chronic illness.…”
Section: Discussionsupporting
confidence: 91%
“…Ninety percent of the 257 participants indicated that they would like to attend future educational sessions delivered by VC and expressed satisfaction about not having to travel for the sessions. 9 The results of the current study corroborate these findings and extend them to an audience of school professionals and content related to chronic illness.…”
Section: Discussionsupporting
confidence: 91%
“…13,14,17,2633 Some studies identified disadvantages that required further improvement. 26,3442 In three cases, the conclusion was that the advantages of teledentistry over the conventional alternative was either unclear, or that the conventional approach had advantages over teledentistry. 4345…”
Section: Resultsmentioning
confidence: 99%